(untitled) (REMUNOM, 2025)
Hospital Dentistry comprises a set of preventive, diagnostic and therapeutic actions for oral and facial diseases or oral manifestations of systemic origin, in patients in a hospital environment, aiming to maintain oral health and improve quality of life. Regulated in January 2024 by the Federal Council of Dentistry, the new specialty seeks to insert the dentist in the hospital environment together with multidisciplinary teams, ensuring comprehensive care and promoting the oral health of hospitalized patients, considering that the oral cavity can be a gateway for several opportunistic infections. The objective of this study was to conduct a literature review on Hospital Dentistry in Brazil, from its inception to the present day, highlighting its importance in preventing health problems. To carry out this study, articles published between 2010 and 2024 were researched on the Pubmed, SciELO, Google Scholar and Virtual Health Library platforms. After conducting this review, there is a general consensus among the existing literature that hospital dentistry has been increasingly gaining ground in Brazil. Little by little, dentists have been seeking their place among professionals in ICUs and highly complex services. Despite the challenges that still exist, the presence of dentists in multidisciplinary teams has proven to be of great importance, whether in maintaining oral health, in the management and treatment of oral conditions that may occur after hospitalization, as well as in the prevention of nosocomial pneumonia and other health problems.